RETRACTED: Short-term responses of Spinach (Spinacia oleracea L.) to the individual and combinatorial effects of Nitrogen, Phosphorus and Potassium and silicon in the soil contaminated by boron - Ma, Jing; Ali, Sajjad; Saleem, Muhammad Hamzah; Mumtaz, Sahar; Yasin, Ghulam; Ali, Baber; Al-Ghamdi, Abdullah Ahmed; Elshikh, Mohamed S.; Vodnar, Dan C.; Marc, Romina Alina; Rehman, Abdur; Khan, Muhammad Nauman; et al. (Frontiers in Plant Science, 2022)
It was aimed to examine the individual and combinatorial role of silicon (Si) and NPK fertilizer mediated growth and physiological functions by alleviating boron (B) toxicity in Spinach (Spinacia oleracea L.). Two weeks old S. oleracea seedlings were subjected to different toxic levels of B i.e., 0, 250 and 500 ppm with different NPK fertilizers [low NPK (30 kg ha-1) and normal NPK (60 kg ha-1)], which were also applied by Si (3 mM). B toxicity induced a substantial decrease in plant growth and biomass, gas exchange characteristics and essential nutrients uptake in S. oleracea seedlings. In contrast, it increased oxidative stress indicators which were also manifested by the activities of antioxidant compounds (enzymatic and non-enzymatic). Moreover, organic acid exudation was also increased with the increase in B contents in the roots of S. oleracea seedlings. The individual and combinatorial application of NPK and Si increased growth-related-attributes, improved photosynthetic machinery, enhanced essential nutrients uptake and also increased the activities of various antioxidant compounds by decreasing the contents of oxidative stress indicators and B uptake in various organs of plants. Our results also advocated that, application of NPK and Si further decrease organic acid contents in the roots of S. oleracea seedlings, which were increased due to B toxicity in the soil. In nutshell, application of NPK and Si improve plant growth by minimizing B contents, organic acid exudation and reduce oxidative stress indicators in the plant parts by increasing the activities of antioxidant compounds.